NATIONAL INSTITUTIONAL FRAMEWORK AND CONSUMER PROTECTION: UNLOCKING THE NEXUS THROUGH SYSTEMATIC LITERATURE REVIEW (Contemporary Journal of Social Science Review, 2025)
Nowadays, institutional framework and consumer protection are considered as one of the most burning topics for researchers and the academicians. This study is an attempt to explore the effective national institutional framework of consumer protection. The study has used systematic literature review to highlight the effectiveness of institutional framework of consumer protection. The findings of the study uncover that, despite having consumer protection laws, enforcement remains weak in many countries due to weak institutional framework. Moreover, inefficiencies and lack of transparency within regulatory bodies undermine consumer trust and law enforcement. The study has suggested that there is a dire need of collaboration between governments, businesses, and civil society to create a holistic consumer protection ecosystem. The topic is still open for other researchers as this study has endeavors to partially explore the importance of institutional framework for consumer protection.